Enhancing Sixth Graders' Mathematical Communication Skills Using the RADEC Learning Model: A Focus on Ratio Concepts - Siti Muhdiati; Wahyu Sopandi; Atep Sujana; Innaka Arina Haq; Ali Juma Khomis (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mathematical communication skills are critical for students to effectively understand and articulate mathematical concepts, directly impacting their numeracy and academic success. This study examines the effectiveness of the RADEC (Read, Answer, Discuss, Explain, Create) instructional model in improving the mathematical communication skills of sixth-grade students. A quasi-experimental design with a quantitative approach was employed, involving 60 sixth-grade elementary students. The experimental group (n = 30; 19 males, 11 females) received instruction through the RADEC model, while the control group (n = 30; 12 males, 18 females) was taught using the Problem-Based Learning (PBL) approach. Data were collected using a test consisting of five open-ended descriptive questions administered as pre- and post-tests. The N-Gain score was used to assess improvement, and the Mann-Whitney U test was applied to evaluate statistical significance. The RADEC group exhibited a moderate increase in mathematical communication skills, whereas the PBL group demonstrated only a low level of improvement. Statistical analysis confirmed a significant difference between the two groups (asymp. Sig. 0.001, α = 0.05), indicating that the RADEC model was more effective. These findings suggest that the RADEC model enhances students’ mathematical communication more effectively than PBL, likely due to its emphasis on active engagement and collaborative learning. The model shows promise as a pedagogical approach and warrants further investigation regarding its impact on other mathematical competencies, including problem-solving, representation, critical thinking, and mathematical connections.